Left ventricular longitudinal strain in professional athletes, a useful tool to detect an athletes hearts?. (25th November 2020) - Bewarder, Y; Kulenthiran, S; Schaefer, O; Lauder, L; Ukena, C; Marshall, R; Hepp, P; Laufs, U; Stoebe, S; Hagendorff, A; Boehm, M; Mahfoud, F; et al.
Abstract: Background: Professional cyclists frequently present with physiological adaptations to endurance exercise with an increase in left ventricular wall thickness and mass. Global longitudinal strain (GLS) is an early and sensitive echocardiographic method to detect left ventricular dysfunction. However, it is unclear whether GLS is able to differentiate between athlete's hearts or different pathological conditions of left ventricular hypertrophy. Methods: A total of 87 professional athletes (37 professional cyclists, 29 professional soccer players, and 21 professional handball players) were compared to 125 patients with different forms of left ventricular hypertrophy (17 hypertrophic obstructive cardiomyopathy (HOCM), 36 hypertensive heart disease (HHD), 35 severe aortic valve stenosis (AVS); 37 untrained individuals served as controls. Examinations were performed between October 2018 to October 2019. All subjects underwent echocardiographic examination, including GLS. Results: In all 212 participants/patients included a preserved ejection fraction >50% (mean 61±7%) was detected. Left ventricular mass index (LVMI) in professional cyclists (165.5±37.1 g/m 2 ) was increased when compared to professional soccer players (97.3±12.4 g/m 2, p<0.001), professional handball players (92.2±15.8 g/m 2, p<0.001) and healthy controls (94.3±20.7 g/m 2, p<0.001), as well as to patients with HHD (129.2±30.0 g/m 2, p<0.001), or AVS (140.1±35.4 g/m 2, p=0.064), but not to patients with HOCM (159.7±39.4 g/m 2, p=0.64). Professional cyclists (−21.0±3.5%) achieved higher average GLS values than professional soccer (−18.4 ± %, p=0.004) or handball players (−18.4 ± %, p=0.021), healthy controls (−19.0±3.0%, p=0.008), HOCM (−15.0±6.5%, p<0.001), HHD (−13.8±5.9%, p<0.001), and AVS (−16.0±7.0%, p<0.001) (Figure 1). Conclusion: In professional cyclists, higher LVMI and average GLS values were detected compared to professional soccer and handball players with lower excessive endurance exercise, as well as untrained healthy controls. Average GLS can help to differentiate between athletes' hearts in professional cyclists compared to pathologic patterns in different diseases characterized by left ventricular hypertrophy with elevated LVMI. Funding Acknowledgement: Type of funding source: None